2009
DOI: 10.1530/eje-08-0687
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife stereotactic radiosurgery of Nelson syndrome

Abstract: Objective: Gamma knife radiosurgery (GKR) can be used as primary or adjuvant therapy for the treatment of an ACTH-producing pituitary tumor after bilateral adrenalectomy, called Nelson syndrome (NS). We have examined the effect of GKR on tumor growth and ACTH-hypersecretion, and characterized the adverse events of this treatment in patients with NS. Design: Cross-sectional follow-up study. First, retrospective data pre-and post-GKR were collected. Patients then underwent a predefined survey including radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 14 publications
(23 reference statements)
1
18
0
6
Order By: Relevance
“…7,43,50,85,70 Vik-Mo et al published a study in which 10 patients with Nelson's syndrome underwent GK treatment. 84 On average, tumor volume decreased by 32% for 9 patients but not at all for 1 patient. Of these 10 patients, ACTH levels decreased for 8 (range 2.0-278 pmol/L) and reached normal range for only 1 patient.…”
Section: Surgical Treatmentmentioning
confidence: 87%
“…7,43,50,85,70 Vik-Mo et al published a study in which 10 patients with Nelson's syndrome underwent GK treatment. 84 On average, tumor volume decreased by 32% for 9 patients but not at all for 1 patient. Of these 10 patients, ACTH levels decreased for 8 (range 2.0-278 pmol/L) and reached normal range for only 1 patient.…”
Section: Surgical Treatmentmentioning
confidence: 87%
“…CRT has been demonstrated to decrease plasma ACTH levels and induce shrinkage of the pituitary tumor in 93.3% of patients with NS (303). The data on the use of GK, the only type of radiosurgery reported in the management of corticotroph tumor progression, are conflicting, and the remission rate represented by tumor growth arrest and/or decline in circulating ACTH levels, ranges from 14 to 100% (319,(441)(442)(443)(444)(445). Although one study showed tumor growth arrest and no tumor regrowth in 100% of patients at 7 years after GK therapy (444), another study showed remission rate after GK to be only 14% (445).…”
Section: Nelson Syndrome or Corticotroph Tumor Progressionmentioning
confidence: 99%
“…The data on the use of GK, the only type of radiosurgery reported in the management of corticotroph tumor progression, are conflicting, and the remission rate represented by tumor growth arrest and/or decline in circulating ACTH levels, ranges from 14 to 100% (319,(441)(442)(443)(444)(445). Although one study showed tumor growth arrest and no tumor regrowth in 100% of patients at 7 years after GK therapy (444), another study showed remission rate after GK to be only 14% (445). GK seems to be more effective in the treatment of corticotroph tumor progression when administered soon after bilateral adrenalectomy and when the anatomical target is clear and discrete (319,443,444).…”
Section: Nelson Syndrome or Corticotroph Tumor Progressionmentioning
confidence: 99%
“…Although one study of Nelson's syndrome patients showed no tumour re-growth at 7 years post GKS therapy (82), a further study showed remission rates post GKS to be only 14% (83). GKS seems to be most effective in Nelson's syndrome when it is administered soon after TBA (82) and when the anatomical target is clear and discrete (less likely with prior surgery, which may render the tumour border indistinct (78,81)). Potential adverse effects of GKS include panhypopituitarism (up to at least 7 years post surgery (84)) and cranial nerve palsies.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 99%